Addition of probiotics on the biofloc system for the improvement of growth performance and health of red hybrid tilapia (Oreochromis spp.) - Mohd Zabidi, Nur Aimi (2021)
Biofloc technology is the aggregation of microorganism bond in a matrix with the aim to improve water quality and as diseases management tools. However, biofloc system can be difficult to manage due to the high microbial load that may be pathogenic or cause no significant effect towards the cultured species. Probiotic addition in biofloc may provide promising results in cultured species and improve the culture system much efficiently from growth of cultured species and resistance to significant diseases. This study was carried out to evaluate the effectiveness of multi-strain probiotics addition in biofloc system and identify microbial composition in biofloc system with and without probiotic addition. Through in vitro analysis, four different probiotics Lysinibacillus fusiformis strain SPS11, Bacillus amyloliquefaciens strain L9, Entrococcus hiriae strain LAB3 and a commercial multi-train probiotic of Lactobacillus sp., Aztobacter sp., Azospirillum sp. (MG1©, Indonesia) at concentration of 108 CFU mL-1 were screened individually and as a mix using well-diffusion assay against Streptococcus agalactiae and Streptococcus iniae at two concentrations; 106 CFU mL-1 and 108 CFU mL-1. The outcome showed that the selected probiotic multi-strain Lysinibacillus fusiformis strain SPS11, Bacillus amyloliquefaciens strain L9 and Entrococcus hiriae strain LAB3 showed antagonistic activity against S. iniae and S. agalactiae with diameter zone of 8.05±0.95 to 10.75±1 mm respectively. A 240 red hybrid tilapia fingerlings with an initial mean weight 50±0.64 mg and a total length of 3.56±0.21cm was used for in vivo assay with a duration of 4 weeks. The fish were cultivated in 6L aquarium with four treatments: biofloc only (B), biofloc enriched with probiotic strain Lysinibacillus fusiformis strain SPS11, Bacillus amyloliquefaciens strain L9 and Entrococcus hiriae strain LAB3 (B+PM), biofloc enriched with commercial probiotic (B+MG1) and freshwater as control. The survival of the fingerlings were higher in B+PM and control (90-91%) than other biofloc treatments (84-89%). The growth performance was significantly higher in biofloc treatments than control (P<0.05). Treatment B+PM had the best specific growth rate (3.73±0.23 % day-1), final body weight (15.07±1.30g) and feed conversion rate (0.76±0.04). Water quality parameters for all treatments were within suitable range for aquaculture. However, biofloc treatments had lower nitrogen concentration (NO2-N, NO3-N and NH4-N). Biofloc+PM had lowest nitrite, NO2-N, Nitrate, NO3-N and ammonia concentration, NH4-N (0.84±0.07 mg L-1, 2.00±0.22 mg L-1, 2.60±0.08 mg L-1) as compared to control (2±0.14 mg L-1, 0.8±0.31 mg L-1, 3.8±0.3 mg L-1). In a challenge test against S. agalactiae, the fingerlings from biofloc treatments B and B+PM showed significantly higher survival (73±1.2% and 83±1.43% respectively) than control (40±0.34%). For microbial composition analysis through metagenomics, biofloc water samples from taken at the end of the tilapia culture. Biofloc treatment showed composition of 18 phyla, from which the most abundant were Proteobacteria, Bacteroidetes, Chlamydiae and Actinobacteria. This study showed multi-strain probiotics of Lysinibacillus fusiformis strain SPS11, Bacillus amyloliquefaciens strain L9 and Entrococcus hiriae strain LAB3 showed great potential in improving water quality, growth peformance, diseases resistance of tilapia and biofloc microbial community. The applicability of this mix may further improve freshwater culture and the ability to control biofloc microbial community.